2007
DOI: 10.1590/s0103-50532007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, chemistry and pharmacology of Croton species (Euphorbiaceae)

Abstract: Croton é um gênero de Euphorbiaceae com cerca de 1300 espécies, amplamente distribuídas em regiões tropicais do Novo e Velho Mundos. Várias espécies há muito tempo desempenham papel importante nos usos tradicionais de plantas medicinais na África, Ásia e América do Sul. Tais usos incluem tratamento de câncer, constipação intestinal, diarréia e outros problemas digestivos, diabetes, feridas externas, febre, hipercolesterolemia, hipertensão, inflamação, vermes intestinais, malária, dor, úlceras e obesidade. Vári… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
334
0
70

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(416 citation statements)
references
References 154 publications
(225 reference statements)
12
334
0
70
Order By: Relevance
“…10 Many pharmacological effects of Croton urucurana have been described in literature, which include wound and ulcer healing, antidiarrhoeic, anticancer, intestinal anti-inflammatory, antioxidant and antirheumatic properties. [11][12][13][14]28 Peres et al 15 reported the antibacterial activity against Staphylococcus aureus and Salmonella typhimurium of the aqueous-EtOH extract, some fractions of the methanolic extract, catechin and acetyl aleuritolic acid obtained from C. urucurana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Many pharmacological effects of Croton urucurana have been described in literature, which include wound and ulcer healing, antidiarrhoeic, anticancer, intestinal anti-inflammatory, antioxidant and antirheumatic properties. [11][12][13][14]28 Peres et al 15 reported the antibacterial activity against Staphylococcus aureus and Salmonella typhimurium of the aqueous-EtOH extract, some fractions of the methanolic extract, catechin and acetyl aleuritolic acid obtained from C. urucurana.…”
Section: Introductionmentioning
confidence: 99%
“…10 Many pharmacological effects of Croton urucurana have been described in literature, which include wound and ulcer healing, antidiarrhoeic, anticancer, intestinal anti-inflammatory, antioxidant and antirheumatic properties. [11][12][13][14]28 Peres et al 15 reported the antibacterial activity against Staphylococcus aureus and Salmonella typhimurium of the aqueous-EtOH extract, some fractions of the methanolic extract, catechin and acetyl aleuritolic acid obtained from C. urucurana.Previous phytochemical analysis of Croton urucurana have identified the presence of acetyl aleuritolic acid, catechin, gallocatechin, sonderianin, β-sitosterol and its glucoside, stigmasterol, campesterol and two novel clerodane diterpenes. 13,15,16 Fucoarabinogalactan, a polysaccharide, has been isolated from the gum exudate of C. urucurana.…”
mentioning
confidence: 99%
“…The huge structural diversity of natural compounds and their bioactivity potential have meant that several products isolated from plants, marine flora and microorganisms can serve as "lead" compounds for improvement of their therapeutic potential by molecular modification. 2,3 Pterodon genus compromises four species native to Brazil: P. abruptus Benth., P. apparucuri Pedersoli, P. pubescens Benth. (P. emarginatus Vog.)…”
mentioning
confidence: 99%
“…O teste Shinoda foi positivo para flavonoides em todos os extratos (Tabela 1). Todas as espécies do gênero Croton (Euphorbiaceae) têm apresentado flavonoides, em sua maioria agliconas de flavonois altamente metoxilados (31).…”
Section: Resultsunclassified